2006
DOI: 10.1111/j.1745-459x.2006.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microwave Blanching on the Flavor of Roasted Peanuts

Abstract: Microwave blanching of peanuts was proposed as an attractive alternative to traditional techniques of blanching, because of energy and time savings. However, the occurrence of a processing‐related off‐flavor has been reported. This study examined the effect of processing factors during microwave blanching on the MC and sensory characteristics of the peanuts. The peanuts reached a range of internal temperatures during microwave blanching treatments between 4 and 11 min. A total offnote attribute was introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…Peanut seeds have high nutritional and commercial value due to their protein, fatty acid, carbohydrate and fi ber content, as well as vitamins, calcium, and phosphorous. Peanut oil is used in cooking and is also employed in the manufacture of margarines, cosmetics, pharmaceuticals and surfactants (Plessis and Steiman, 2004;Schirack et al, 2006;Nakai et al, 2008;Rodriguez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Peanut seeds have high nutritional and commercial value due to their protein, fatty acid, carbohydrate and fi ber content, as well as vitamins, calcium, and phosphorous. Peanut oil is used in cooking and is also employed in the manufacture of margarines, cosmetics, pharmaceuticals and surfactants (Plessis and Steiman, 2004;Schirack et al, 2006;Nakai et al, 2008;Rodriguez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…lipase and lipoxygenase, have not yet been fully elucidated. As reported for peanuts, oven roasting reduced oxidative activity of lipase and lipoxygenase (Adelsberg & Sanders, 1997;Schirack et al, 2006). In another work (Sanders et al, 1999), the same process was reported to slightly increase these enzymatic activities with little impact on shelf life.…”
mentioning
confidence: 64%
“…Indeed, as reported by Schirack et al (2006) in their experiment on peanuts peeling, shorter heating times also lead to greater nutrient retention and better quality characteristics such as texture and flavour. Indeed, no changes in walnut, hazelnut and almond kernel lipids were detected after microwave roasting at full power for 180 s (Momchilova & Nikolova-Damyanova, 2007).…”
mentioning
confidence: 95%
“…Oxidative changes followed by oxidized, cardboard, painty, and fishy flavors are the most common deteriorative defect in high fat products such as peanuts. The main reason for oxidative changes in peanuts is the autoxidation of linoleic acid, which is also known as flavor reversion [22,23]. The shelf life descriptive study results (Table 6) showed no indication of any oxidative changes in any of the samples over the storage period of six weeks (<0.33 on a scale of 15).…”
Section: Shelf Life Descriptive Sensory Analysis Of Blanchedmentioning
confidence: 92%